2018
DOI: 10.1136/bmjsem-2018-000342
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Shoulder Symptom Modification Procedure and association of within-session and between-session changes with functional outcomes

Abstract: BackgroundDespite being a common problem, there is considerable diagnostic uncertainty with regard to shoulder pain. This uncertainty relates to the reliability and validity of current examination tests. The Shoulder Symptom Modification Procedure (SSMP) has been proposed as an alternative to existing approaches.ObjectiveTo evaluate interclinician reliability of the SSMP and the association of within-session and between-session changes on clinical outcome at 1 week, and at 1 and 3 months.DesignA single-centre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The primary outcome (QuickDASH) and most other secondary outcomes of interest showed no between‐group differences over time. This is consistent with other studies showing that within‐session changes do not necessarily equate to longer‐term improvements in shoulder pathology (Meakins et al., 2018). This finding contrasts with the short‐term predictive capacity of immediate effects in the literature.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The primary outcome (QuickDASH) and most other secondary outcomes of interest showed no between‐group differences over time. This is consistent with other studies showing that within‐session changes do not necessarily equate to longer‐term improvements in shoulder pathology (Meakins et al., 2018). This finding contrasts with the short‐term predictive capacity of immediate effects in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…Previous work has addressed SAPS and found that a large within‐session effect for perceived improvement as determined by a ≥5 GRoC did not correlate to functional change scores (J. C. Garrison et al., 2011). A second study found a poor correlation between within‐session pain score changes and 1‐ or 3‐month pain outcomes (Meakins et al., 2018). A strong correlation from within‐session change scores to 1‐week, moderate to 1‐month, and fair to 3‐month functional outcomes (Meakins et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the authors acknowledged that the efficacy of the Shoulder Symptom Modification Procedure (SSMP) in treating shoulder pain was yet to be established. The other more recent study [ 175 ] reported moderate inter-rater reliability but found the association between within-session and between-session changes in pain regarding treatment efficacy for the Shoulder Symptom Modification Procedure (SSMP) to be insufficient. The authors consequently concluded that the Shoulder Symptom Modification Procedure (SSMP) was not reliable or valid for managing shoulder pain.…”
Section: Assessmentmentioning
confidence: 99%
“…scapular dyskinesis test) and ( 4) lower extremity physical performance tests (e.g., single leg balance). Some controversy exists regarding the use of symptom modification tests 39 and scapular dyskinesis tests 67 . Additionally, the star excursion balance test, which did not meet consensus, appears to be the only lower extremity physical performance test correlated with shoulder injury risk.…”
Section: Physical Examinationmentioning
confidence: 99%